Congenital Adrenal Hyperplasia and Ehlers-Danlos Syndrome - Marino, Roxana; Moresco, Angélica; Perez Garrido, Natalia; Ramirez, Pablo; Belgorosky, Alicia (Frontiers in Endocrinology, 2022)
Congenital adrenal hyperplasia (CAH) secondary to 21-hydroxylase deficiency is an autosomal recessive disorder. The 21-hydroxylase enzyme P450c21 is encoded by the CYP21A2 gene located on chromosome 6p21.33 within the HLA major histocompatibility complex. This locus also contains CYP21A1P, a non-functional pseudogene, highly homologous to the CYP21A2 gene. The other duplicated genes are C4A and C4B, encoding two isoforms of complement factor C4, the RP1 gene encoding a serine/threonine protein kinase, and the TNXB gene, encoding an extracellular matrix glycoprotein tenascin-X (TNX). The TNX plays a role in collagen deposition by dermal fibroblasts and is expressed in the dermis of the skin and in the connective tissue of the heart and skeletal muscle. Misalignment may occur during meiosis generating large gene deletions or gene conversion events resulting in chimeric genes. Chimeric recombination may occur between TNXB and TNXA, and three TNXA/TNXB chimeras that differ in the junction site (CH1 to CH3) and result in a contiguous CYP21A2 and TNXB gene deletion, named CAH-X syndrome, have been described. TNXB deficiency is associated with Ehlers Danlos syndrome (EDS). EDS comprises a clinically and genetically heterogeneous group of connective tissue disorders. As molecular analysis of the TNXB gene is challenging, the TNX-deficient type EDS is probably underdiagnosed. In this minireview, first the different TNXB-gene molecular analysis strategies available are being addressed. In addition, copy number variations and genetic status of the TNXB gene in different cohorts are discussed. Next, clinical features of EDS are described and clinical recommendations for long-term follow-up are discussed.